Usare Gramsci. Una prospettiva pedagogica. - Ausilio, Manuela (International Gramsci Journal, 2023)
This is an Italian-language review by Manuela Ausilio of Massimo Balducci’s recent book Usare Gramsci. Una prospettiva pedagogica (Roma, Carocci). It looks at Gramsci’s relevance to current pedagogy and includes a critical examination of previous writers on Gramsci and educational topics, with a glance at others who adopted similar stances to his.